Gastroretentive systems - a proposed strategy to modulate anthocyanin release and absorption for the management of diabetes - Celli, Giovana Bonat; Kalt, Wilhelmina; Brooks, Marianne Su-Ling (Drug delivery, 2016)
Several reports have indicated a positive correlation between the consumption of anthocyanins (ACN) and biomarkers relating to the improvement of type 2 diabetes (T2D). However, the results from in vitro studies often do not translate into clinical evidence. Potential causes of these discrepancies are experimental conditions that lack physiological relevancy; extensive degradation of these compounds in vivo due to changes in pH and metabolism; and a short residence time in the absorption window in relation to the absorption rate. Here, gastroretentive systems (GRS) are proposed as a strategy to overcome the limitations in ACN delivery and to reduce the existing bench-to-subject gap. This review summarizes recent literature on the use of ACN for the management and control of T2D, followed by GRS platforms to promote a sustained release of ACN for increased health benefits.